Africa and its Quest for a Linguistic Integration (Global Journal of Human-Social Science, 2015)
Language has been a vast field of study in which many brains have been functioning so as to demystify the different predicaments it poses to its speakers and hearers. Since language is taken to be the haven of identities and global integration, it has always been a priority for a country to maintain a unifying language via which all its people would be identified and develop a sense of nationhood. A case in point is Africa, which is still facing a host of challenges appertaining to either the national or regional integration of its multilingual people. Because Africa is teeming with hundreds of languages, the languages of the ex-colonizers (English, French or Portuguese... etc) have played major roles in bringing, to some extent, the Africans together. Still, many Africans have been concerned with the fact that the ex-colonial languages constitute nothing but unifying linguistic options made at the disposal of only the African elites rather than the masses. In this sense, African leaders sensed the necessity of holding a unified African world which would endure the outside economic and political challenges, especially after the era of colonialism. In this respect, this paper is an attempt to prescribe some antidotes for such African linguistic alchemy.
Keywords: horizontal integration – vertical integration – linguistic alchemy